Millennial Interpretation Model of the Triqul Surahs in The Qur’anything by Ismail Al-Ascholy: A Perspective of H. G. Gadamer’s Hermeneutics - Intan Paramisti; Luthviyah Romziana (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The religious condition of the millennial generation in the digital era is characterized by the openness of information, the intensity of social media use, as well as fatigue toward modes of Islamic teaching that are formal, rigid, and less communicative. One relevant approach to address this issue is Hans-Georg Gadamer’s hermeneutics. This study is a library research employing a qualitative approach, using the concepts of Wirkungsgeschichte (history of effect), pre-understanding, fusion of horizons, and application (Anwendung). The findings indicate that pesantren background, the oral culture of Madura, and Ismail’s engagement in the digital sphere shape a productive pre-understanding that gives rise to a strong adab? ijtim?‘? exegetical style, marked by contextual bi al-ra’yi interpretation and a popular–humorous tone. Surah al-Ikhl?? is read as a critique of the phenomenon of “semi-gods” and ego-idolatry; al-Falaq is interpreted as a “fissure” in the dynamics of life and as a critique of envy and competition in social media culture; while al-N?s is understood as a response to whisperings, inner anxiety, and the psychological pressures of the digital age. Thus, The Qur’anything presents a model of popular Qur’anic exegesis that bridges the authority of pesantren tradition with the spiritual and psychological needs of the millennial generation, while reaffirming the Qur’an as a living text that remains relevant to contemporary religious problems.